DETERMINAN KEPUTUSAN PETANI MENJUAL PRODUKSI KARET DI PASAR LELANG DAN NON LELANG DI KECAMATAN LUBUK RAJA KABUPATEN OGAN KOMERING ULU - ema pusvita (JASEP, 2022)
This study examines the determinants of farmers' decisions to sell rubber production in the auction and non-auction markets in Lubuk Raja District, OKU Regency. The purpose of this study is (1) to measure the level of satisfaction of farmers who sell their rubber production to the auction and non-auction markets. (2) analyze the factors that determine the decision of farmers to sell rubber production to the auction market. The research method in this study is a survey method. The sampling method used was the disproportionate stratified random sampling method. The number of sample farmers taken in this study is classified as layer I, namely farmers who sell to the auction market with a total of 30 people. While the second layer is farmers who sell to non-auction markets with a sample of 30 people. Data analysis uses score calculations and logistics using SPSS. The results of this study are the level of satisfaction of farmers who participate in the auction market is in the high category or very satisfied, while the level of satisfaction of farmers who sell production to non-auction is in the medium or satisfied category. This happened because the auction market received more information about the rubber trading system and service and the selling price received was better than in the non-auction market. The economic factor that most determines the decision of farmers to sell their products to the auction market and to the non-auction market is income and the social factor is education.Keywords: Determinant, decision, rubber,satisfaction